Baseline assessment of underwater noise in the Ria Formosa - Soares, C (2020)
The Ria Formosa is a sheltered large coastal lagoon located on the Atlantic South Coast of Portugal, that has been classified as a natural park since 1987. The lagoon hosts a diverse and abundant fish community and other species of commercial importance. Several economical activities are supported by shipping, and as such, vessel traffic within the Ria Formosa lagoon is very intense at some locations during particular seasons of the year, creating high levels of underwater noise. Recently, strong efforts are being made to turn the main inlet of the lagoon, the Faro-Olhão Inlet, a testing site for small scale tidal stream turbines, which will bring an additional source of underwater noise. Underwater noise can be one of a number of factors causing habitat degradation, as it can perturb fish behavior and cause physiological damage. Therefore, in order to comply with underwater noise pollution regulations, tidal energy technology developers are very interested in minimising the introduction of acoustic energy in the environment during the operation of their devices. Under the scope of project SCORE, which involved the deployment and operation of a floating tidal energy converter, this paper presents and discusses the first baseline noise monitoring performed at Ria Formosa. The acoustic data were collected in two occasions over several days, one in the winter and the other in the summer, in 2017. The obtained analysis results highlight the potential impact of the intense boat traffic in Ria Formosa, and the wide range of sound levels introduced in that ecosystem, and the high diurnal and seasonal variability.